Social media to understand the endometriosis patient journey: Listening to influences driving treatment choices - Vicky Britton; Alexis Sohn; Nicole T Ansani; Brett Hauber; Michele Cole; Martine C Maculaitis; Ruth Kim (Women's Health)
Background: Previous research has identified treatment attributes and outcomes for endometriosis patients, highlighting the need for tailored interventions to improve patient care. These studies emphasize the need to understand patient experiences, focusing on pain symptoms and factors that impact quality of life. Objectives: This study aimed to provide an in-depth description of patient experiences with endometriosis related to treatment attributes and outcomes, including three key types of pain symptoms: Non-menstrual pelvic pain, dyspareunia, and dysmenorrhea, and non-pain factors such as out-of-pocket costs. Design: In this retrospective qualitative study, 47,745 public social media posts from the United States from December 2021 to December 2022 were analyzed. Methods: Boolean queries were created incorporating criteria to identify public posts referencing endometriosis and language indicative of patients expressed in the first-person point of view. Data were summarized via descriptive statistics. Results: Findings confirmed the relevance of non-menstrual pain, dyspareunia, and dysmenorrhea for treatment decision-making. Dysmenorrhea, described as excruciating and debilitating, was the most discussed symptom (10% of posts) followed by dyspareunia (3% of posts), with emotional and physical impacts detailed. Non-menstrual pain was specified in 1% of posts, including the follicular, ovulatory, and luteal phases of the menstrual cycle. Key themes that emerged organically included the impact of endometriosis on daily functioning, mental health, intimacy, fertility, and the role of online misinformation. Discussions detailed the struggle to balance symptom relief with long-term solutions, and frustration with diagnosis. Conclusion: The current study highlights the difficulties patients experience with dysmenorrhea, dyspareunia, and non-menstrual pain and the challenges to treatment decisions. The relevance of social media for patient expression of their disease experience, the importance of recognizing the individualized needs of patients necessitating their active involvement in treatment decision-making, and the need for education about treatment options beyond surgery also emerged in the findings.